TEKNIK ANALISIS SISA MANUSIA - Harry Widianto (Berkala Arkeologi, 2000)
It is almost certain that the findings of human remains in the context of archaeological data in Indonesia will only range in two species, namely Homo erectus and Homo sapiens. Morphologically, these two types are very easy to distinguish in their cranio-facial aspects, but very difficult for their infra-cranial components. Due to the very limited nature of Homo erectus data which is often in fragmentary form and accompanied by the importance of observing every morphological aspect of this species because it has an evolutionary meaning which is very valuable for its information in the study of the process of human evolution. Homo erectus analysis has to be done in more detail, more carefully, and more thoroughly, to arrive at any interpretation that can be drawn.